Improving flexural strength and toughness of geopolymer mortars through additively manufactured metallic rebars. (15th July 2018) - Farina, Ilenia; Modano, Mariano; Zuccaro, Giulio; Goodall, Russell; Colangelo, Francesco
Abstract: This paper presents the results of an experimental study on the flexural reinforcement of a geopolymer mortar through additively manufactured metallic rebars. A mortar employing a geopolymer binder with low calcium content fly ash is reinforced with Ti6Al4V rebars additively manufactured though electron beam melting. The effectiveness of reinforcements realized with rebars featuring either smooth or rough surface profiles is studied through three-point bending tests and post-test microscopy analysis. The given experimental results highlight micro and macroscale pullout failure mechanisms in specimens reinforced with rebars showing cylindrical embossments on the lateral surface, which remarkably improve the flexural strength and the interfacial bond strength of the analyzed mortar. The role played by the surface roughness of the reinforced elements on the bond-slip response of the matrix-rebar interface is highlighted, while drawing comparisons with available literature results on cement mortars.